Peran Guru IPS Dalam Mengembangkan Kesadaran Sosial Siswa Sekolah Dasar - Raziska Ibrahimi (Journal of Humanities, Social Sciences, and Education, 2026)
Social awareness is an individual’s ability to understand, appreciate, and respond positively to social conditions in their surrounding environment. At the elementary school level, social awareness is a crucial aspect in shaping students’ character to be caring, responsible, tolerant, and able to live harmoniously in diverse society. Social Studies (IPS) plays a strategic role in developing social awareness because it includes materials related to social life, community interaction, and human values. However, previous studies tend to discuss teachers’ roles in general terms without systematically synthesizing how social studies teachers specifically develop students’ social awareness, indicating a research gap that needs further exploration. This study aims to critically synthesize and analyze the role of social studies teachers in developing elementary students’ social awareness through a literature review approach. The method used is a library research study by analyzing scientific articles, national journals, and relevant sources. Data were analyzed descriptively and qualitatively through identification, reduction, categorization, and interpretation processes. The results show that social studies teachers act as facilitators, role models, motivators, contextual learning managers, and agents of social change. Social studies learning that is active, contextual, and based on real-life experiences has been proven to enhance students’ empathy, cooperation, tolerance, responsibility, and social awareness. These findings emphasize that teachers’ instructional design competence is a key determinant in strengthening students’ social awareness, beyond the influence of learning materials alone.